Pengaruh Model Pembelajaran Cooperative Script Berbantuan Mind Map terhadap Hasil Belajar Siswa tentang Biologi - Buntu, Amalia; Rauf, Abd; Agni, Raya (Jurnal Kreatif Online, 2020)
The purpose of this study was to describe the effect of the mind map-assisted cooperative script learning model on student learning outcomes on biology subject. Learning was carried out online during the COVID-19 pandemic. The research was conducted in the academic year 2020/2021 in odd semesters. This study used a quasi-experimental method with a pretest posttest control group design. This study used 1 control class and 1 experimental class. The number of students were 19 and 21 in the experimental and control class, respectively. To collect the data, a 20-question learning outcome test was used. The research activities were carried out 4 times with 2 tests and 2 learning activities. Research data were analyzed using t-test and Mann Whitney test. The mean difference of the pretest results showed that sig 0.43> 0.05, this indicated that there was no difference in the two groups. The results of the hypothesis test of the posttest showed that Asymp. Sig 0.04 <0.05, with an average posttest score of the experimental class was 11.52 and an average score of the control class learning outcomes was 9.2. The results of this study revealed that the cooperative script learning model assisted with mind maps has a positive effect on student learning outcomes.